Simultaneous ozone and granular activated carbon for advanced treatment of micropollutants in municipal wastewater effluent. (November 2019) - Vatankhah, Hooman; Riley, Stephanie M.; Murray, Conner; Quiñones, Oscar; Steirer, K. Xerxes; Dickenson, Eric R.V.; Bellona, Christopher
Abstract: The main objective of this study was to compare the efficacy of ozone (O3 ) and O3 with granular activated carbon (GAC) (O3 /GAC) at pilot-scale for the enhanced removal of micropollutants (MPs) from wastewater effluent. The results revealed enhanced removal of tris (2-carboxylethyl) phosphine (TCEP), sucralose, and meprobamate during the O3 /GAC treatment experiments compared to the sum of their removal during isolated ozonation and GAC adsorption experiments. The long-term O3 /GAC experiment showed the promotive effect of GAC substantially decreased after 20 h of O3 exposure. This decreased performance correlates with changes to GAC surface properties caused by O3 . After 6 h of operation, O3 initially led to an increase in Brunauer-Emmett-Teller (BET) surface area on the GAC improving the elimination level of investigated MPs (except N-nitrosomorpholine (NMOR)). However, after 20 h of exposure, O3 ultimately caused structural damages to the GAC surface, decreased the BET surface area in the final stages of the experiment, and a 4-fold increase in O1s :C1s ratio on the GAC surface was observed due to an increase in surface acidic functional groups caused by O3 treatment. Highlights: Simultaneous use of ozone and granular activated carbon treatment (O3 /GAC) was employed to treat municipal wastewater effluent The application of O3 /GAC initially enhanced the removal of ozone-refractory micropollutant. The promotive effect of O3 /GAC decreased over time. The impact of O3 on the surface property of GAC was investigated